Managing Africa's Resourcs for Prosperity Presentation by Prof. Paul Collier - UONGOZI Institute (Dar es Salaam UONGOZI Institute, 2012)
Paul Collier is a Professor of Economics and Director of the Center for the study of African Economies at Oxford University and a former director of Development Research at the World Bank. He is known world-wide for his three thought provoking books: 'The Plundered Planet', 'The Bottom Billion', and 'Wars, Guns and Votes: Democracy in Dangerous Places', Collier regularly travels around the world to advise governments and international organisations on this issue, and to speak publicly. He writes regularly for the Guardian, Washington Post, the New York Times, Financial Times, and Wall street Journal.
it runs for 30 mins
Keywords: Natural Resources